The thermal physiology of Stenopelmus rufinasus and Neohydronomus affinis (Coleoptera: Curculionidae), biological control agents for the invasive alien aquatic weeds Azolla filiculoides and Pistia stratiotes respectively - Mvandaba, Sisanda F (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2018)
Water lettuce, Pistia stratiotes L. (Araceae), and red water fern, Azolla filiculoides Lam. (Azollaceae), are floating aquatic macrophytes that have become problematic invaders in numerous South African waterbodies. Two weevils, Neohydronomus affinis Hustache 1926 (Coleoptera: Curculionidae) and Stenopelmus rufinasus Gyllenhal 1936 (Coleoptera: Curculionidae), are successful biological control agents of these two species, respectively, in South Africa. However, nothing is known about the thermal physiology of these two species Therefore, the aim of this study was to investigate the thermal physiologies of these two species to explain their establishment, distribution and impact in the field. Laboratory based thermal physiology trials showed that both weevils were widely tolerant of cold and warm temperatures. The CTmin of N. affinis was determined to be 5.5 ± 0.312°C and the CTmax was 44 ± 0.697°C, while the CTmin of S. rufinasus was 5.4 ± 0.333°C and the CTmax was 44.5 ± 0.168°C. In addition, the lower lethal temperatures were -9.8 ± 0.053°C and -7.2 ± 0.19°C, and the upper lethal temperatures were 42.8 ± 0.053°C and 41.9 ± 0.19°C respectively. These results suggest that both species should not be limited by cold winter temperatures, as previously thought. This is evident in the field, where S. rufinasus has established widely on A. filiculoides, despite local cold climates in some areas of the plant's distribution. Even though N. affinis has a similar thermal range, and should therefore theoretically reflect a similar distribution to S. rufinasus throughout South Africa, its distribution is limited by the range of its host, which is restricted to the warmer regions of the country, as is its biocontrol agent. Using the reduced major axis regression method, the development for N. affinis was described using the formulay=12.976x+435.24, while the development of S. rufinasus was described by y=13.6x+222.45. These results showed that S. rufinasus develops much faster, in fact almost twice as quickly, than N. affinis. Using these formulae and temperature data obtained from the South African Weather Service, N. affinis was predicted to complete between 4 and 9 generations per year in South Africa, while S. rufinasus was predicted to complete between 5 and 14 generations per year around the country. This study showed that although the native range of these two species is warm temperate to tropical, they possess sufficient thermal plasticity to not only establish, but also damage their respective host plants in far cooler climates. Thus, in South Africa N. affinis and S. rufinasus are limited by the distribution of their target weeds and not climate.
Keywords: Beetles -- South Africa; Curculionidae -- South Africa; Azolla filiculoides -- South Africa; Water lettuce -- South Africa; Aquatic weeds -- Biological control -- South Africa; Stenopelmus rufinasus; Neohydronomus affinis